Detection of In-Vitro Antibacterial Activity of Tinospora cordifolia Leaf Extracts against Multidrug Resistant- Staphylococcus aureus Isolated from Diabetic Foot Infections: Antibacterial Activity of Tinospora cordifolia Leaf Extracts - Mahmood, Sehrish; Khan, Muhammad; Ali, Akhtar; Ismail, Muhammad Owais; Mohyuddin, Samina; Arif, Humaira (Pakistan Journal of Health Sciences, 2024)
The manifestations of diabetes are always a great challenge to the medical practitioners and one of its challenging ones are the Diabetic Foot Infection (DFI). There are multiple ways of managing this condition such as using antibiotics to eliminate bacteria and boosting the patient’s intrinsic factors, for example, through blood glucose optimization. DFIs are difficult to treat nowadays because of antibiotic resistance; as a result, scientists have turned to medicinal plants for finding drugs against Multi-Drug Resistant (MDR) bacterial strains. Tinospora cordifolia is a promising plant with untapped wealth of chemical compounds with high therapeutic potential. These biologically active metabolites work together through different mechanisms causing antibacterial action against the MDR strains. Objective: To assess the antibacterial potential of Tinospora cordifolia Leaf Extract (TcLE) against MDR-Staphylococcus aureus isolated from pus samples of patients with DFIs. Methods: In-vitro experimental study conducted in Ziauddin University from December 2022 to September 2023. Extraction of TcLE was done using a rotary evaporator. The antibacterial activity of TcLE was evaluated by the Agar well diffusion assay. Results: Eight different doses were prepared in 10% DMSO using TC’s ethanolic leaf extracts. Growth of MDR-Staphylococcus aureus strain was inhibited by TcLE at the tested concentration of 250 mg/ml, which was the MIC (the lowest concentration of TcLE which suppressed the growth of MDR-Staphylococcus aureus strains). Conclusion: TcLE showed antibacterial activity against MDR-Staphylococcus aureus, thus establishing it as a potential lead compound source of anti-staphylococci drugs.